Targeted and personalized immunotherapy in lung adenocarcinoma: single-cell RNA sequencing of MAFF+ tumor cells and the therapeutic potential of FOS - Cheng, Xiangsong; Chen, Shu; Fu, Yilong; Jiang, Runze; Jing, Yanlong; Zhao, Bizhu; Guo, Dong; Wang, Liangyu; Ye, Zi; Li, Yumeng; Chen, Xianliang (Frontiers in Immunology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) was a major cause of cancer-related mortality globally. Despite advancements in immunotherapy and targeted therapies, clinical outcomes were still limited by tumor heterogeneity and treatment resistance. The transcription factor (TF) FOS, a key component of the AP-1 complex, was linked to tumor progression and therapy resistance in various cancers, but its precise mechanisms remained unclear, and its role in lung adenocarcinoma (LUAD) was unknown. We investigated the tumor microenvironment (TME) of LUAD using single-cell RNA sequencing (scRNA-seq) to identify potential therapeutic vulnerabilities and FOS-driven mechanisms.MethodsWe identified fourteen cell types by analyzing scRNA-seq data from LUAD samples (GSE164789) using Seurat (v4.4.0) and Harmony for batch correction. InferCNV was utilized to characterize the tumor cell subtypes after they were clustered using marker genes. CytoTRACE and Monocle were used to create pseudotime trajectories in order to map differentiation states. CellChat revealed intercellular communication networks, while SCENIC identified TF regulatory modules. The CCK-8, Edu, Transwell, and wound healing assays showed that FOS knockdown functionally validated A549 and NCI-H1975 cells. Furthermore, a prognostic model was developed.ResultsWe discovered that invasive LUAD was dominated by a highly stem-like C0 MAFF+ tumor cell subtype that produced chemokines and activated lipid metabolism. These cells stimulated immunosuppression and tumor-associated macrophage (TAM) differentiation by interacting with macrophages via MIF-(CD74+CD44) signaling. Experiments using FOS knockdown demonstrated its role in maintaining invasion, migration, and proliferation. Using the MTRS model, patients were categorized into high- and low-risk cohorts, high-risk patients exhibited unique drug sensitivities. Immunoprofile analysis revealed higher M1 macrophages in high-risk patients, suggesting that FOS inhibition could repolarize TAMs and enhance immunotherapies.ConclusionOur studies show that FOS is a main regulator of C0 MAFF+ TCs in LUAD, polarizing macrophages via MIF and rewiring lipid metabolism to support cancer. The MTRS model offers clinical value for risk assessment even if FOS inhibition shows promise as a therapeutic approach to raise immunotherapy efficacy. Targeting the FOS could cause TME immunosuppression to be disrupted, thus LUAD presents a fresh precision oncology approach.